Thrombin, protein C, and protein S values in mother-infant dyads in the postpartum period - Maria Garrido-Barbero; Juan Arnaez; Ana Martín-Ancel; Hermenegildo González; Alfredo García-Alix (Elsevier, 2023)
Introduction: The objective of the study was to establish the normal range for the levels of antithrombin (AT), protein C (PC), and protein S (PS) in the first week post birth in mother-infant pairings, adjusting for obstetric and perinatal factors, based on 2 different laboratory methods. Methods: Determinations were carried out in 83 healthy term neonates and their mothers, establishing 3 postpartum age groups: 1−2 days, 3 days, and 4−7 days. Results: There were no differences in the levels of any of the proteins between the different age groups in neonates or mothers in the first week post birth. The adjusted analysis found no association with obstetric or perinatal factors. The AT and PC levels were higher in mothers compared to infants (P < .001), while the PS levels were similar in both. Overall, the correlation of maternal and infant protein values was poor, except for the levels of free PS in the first 2 days after delivery. Although we found no differences based on which of the 2 laboratory methods was applied, the absolute values did differ. Resumen: Introducción: El objetivo fue establecer valores de normalidad de antitrombina (AT), la proteína C (PC) y la proteína S (PS) dentro de la primera semana después del nacimiento en el binomio madre-recién nacido, ajustados por factores obstétricos y perinatales, según dos métodos de laboratorio diferentes. Métodos: Se realizaron determinaciones en 83 neonatos a término sanos y sus madres, con tres grupos de edad posparto: días 1-2, 3 y 4-7. Resultados: No hubo diferencias para ninguna de las proteínas en los distintos grupos de edad de los neonatos y las madres dentro de la primera semana posparto. El análisis ajustado no mostró ninguna asociación con factores obstétricos o perinatales. Los valores de AT y PC en las madres fueron mayores que en los neonatos (P < 0,001), mientras que la PS mostró valores similares. La correlación global de los valores entre los pares madre-recién nacido fue escasa, salvo para la PS libre en los en los siguientes dos días al parto. Aunque no se encontraron diferencias entre los dos métodos de laboratorio, los valores absolutos fueron diferentes.